Psychic suffering during the covid-19 pandemic: an existential analysis on the materiality of life and on the use of technology - Melo, Daniel (2021)
The objective is to discuss the relationship between the materiality of life, the use of technology and the psychological distress during the Covid-19 pandemic. It is a theoretical discussion that takes the existentialist understanding of the human condition as the dialectic between the material condition (the subject as a body-performance-of-subjectivity before the Other), and consciousness as an absolute of subjectivity in its nadificating dynamics. Psychic suffering is an expression of the way the contemporary subject experiences the paradigm of technology in the face of the health crisis arising from the pandemic. The fundamental notions of existentialism are used –conscience, anguish, Other, situation– in order to present the relationship between what is called here the materiality of life, psychological suffering and the pandemic. There is a compromise in the materiality of life in the experience of interpersonal and work relationships mediated by technology. Social isolation as a means of coping with the pandemic is a critical issue and crosses contemporary psychological suffering.